Open Access Repositories As An Accelerator For Open Journal Systems And Enhancer For The SA-SDGs HUB: South African Perspective - Matizirofa, Gallant Lazarus; Selematsela, Daisy (My University, 2023)
OA repository development in South Africa is driven by the CHELSA since 2003. A national Electronic Theses and Dissertation platform was developed to assist with the challenges experienced by academic libraries, i.e. requisite skills and inadequate infrastructures. South Africa Open Access adoption among universities is progressing, while the government funding agency (NRF) released an open access statement (2015) that required funded researchers to deposit their articles into an OA repository with a 12 months embargo period. But in the absence of OA monitoring indicators and implementation, academic libraries through their institutional support have championed and implemented their OA policies while there is no national repository portal. Only aggregated metadata from ETDs is harvested from a few repositories effectively. The purpose of this presentation is to promote COAR's Next Generation Repositories elements through a nationally distributed network of research repositories. Collectively, a national networked infrastructure for scholarly communication, build on top of layers of value-added services can transform a system, making it more research-centric, and open to and supportive of innovation. Networked repositories build additional services, i.e. web-centric interoperability, a set of common technologies, protocols, and behaviours, to assist in fast-tracking and enhancing alternative metrics for the national SDG Hub and promote social justice.
Keywords: Open Access Repositories; Open Journal Systems; SDGs